Analisis Bibliometrik: Perkembangan Penelitian dan Publikasi Kualitas Pelayanan Rumah Sakit Jiwa dalam Tiga Dekade - Ratnawaty, Yenny; Alfatih, Andy; Lionardo, Andries (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to find out the trend of scientific publications on the topic of mental hospital service quality over the last three decades, including the description of the network structure of previous researchers and their institutions. The approach method used in this research is the bibliometric analysis method. Bibliometric analysis methods are used to provide an overview of the progress and development of knowledge in studying certain research topics. In carrying out bibliometric analysis, this research uses data from journals or articles indexed by Scopus and visualizes it using the VOSviewer application version 1.6.20. Data collection in this study used keywords by entering the query: ((TITLE-ABS-KEY("psychiatric hospital") AND TITLE-ABS-KEY("service") AND TITLE-ABS-KEY(quality))). A search yielded 681 documents discussing the topic of mental hospital service quality from 1973 to 2023. The most dominant subject area was the theme "medicine" with 555 articles. As a result of the research, the most publications on the topic of mental hospital service quality in 2020 were 38 articles. The country that has published the most on this topic is the United States with 155 articles, while the researcher with the greatest productivity is Dr Hermann SpieÃŸl Bezirksklinikum Regensburg, a researcher from Germany who has published 9 scientific articles. The development of publications was analyzed based on keywords (co-words). The results were that there were 8 clusters formed from the network visualization results.